Nutrient value and stability of chloroplast-rich fraction (CRF) material from pea vine haulm, and the role of galactolipolytic enzymes during digestion - Wattanakul, Jutarat (2020)
Underutilised green plant material is a rich source of chloroplasts, organelles in plants and other photosynthetic organisms, which are responsible for the conversion of light energy into chemical energy. The removal of intact chloroplasts from their cell wall confinement offers a novel way to obtain lipophilic nutrients and galactolipids from green biomass, especially carotenoids, vitamin E, and galactolipids (the main membrane lipids in plants and they represent a major source of the essential alpha-linolenic acid (18:3, ALA)). We have developed a physical method of recovering a chloroplast-rich fraction (CRF) from postharvest, pea vine field residue (haulm) by using slow-screw twin-gear juicer without added water. The CRF from pea vine haulm (PVH), like CRF from spinach leaves, is a good source of lipophilic nutrients, including beta-carotene (provitamin A), lutein, alpha-tocopherol (vitamin E), phylloquinone (vitamin K), and essential fatty acids.